The Therapeutic Power of Reading: A Qualitative Analysis of Bibliotherapy in Islamabad - Syeda Fatima Hasan Gilani; Sofia Shahid, (Dialogue Social Science Review (DSSR), 2025)
Bibliotherapy, which involves the purposeful use of reading materials to enhance psychological and emotional well-being, has surfaced as an affordable and accessible intervention that can serve as a complement to conventional mental health strategies. In Pakistan, where access to mental health services is constrained and stigma frequently hinders individuals from pursuing professional assistance, bibliotherapy presents a subtle and culturally flexible alternative. This qualitative study investigates the therapeutic benefits of bibliotherapy for adults in Islamabad, emphasizing their lived experiences, emotional and cognitive transformations, and the fundamental processes that facilitate personal development through bibliotherapy. A targeted sample of 26 adults from the general community of Islamabad was gathered through public libraries, book clubs, and community centers. Every participant had been involved in either structured or self-directed bibliotherapy for a minimum duration of three months. Semi-structured interviews were carried out in both English and Urdu, followed by transcription and thematic analysis utilizing Braun and Clarke’s six-phase framework. Three central themes emerged from the data: (1) Emotional Resonance, where participants identified with characters or narratives reflecting their own struggles, leading to validation and emotional release; (2) Cognitive Reframing, in which reading encouraged alternative perspectives and challenged negative thinking patterns; and (3) Self-Reflection and Growth, encompassing increased self-awareness, empathy, and positive behavioral change. The findings indicate that bibliotherapy in Islamabad contributes to emotional regulation and cognitive flexibility while also enhancing a sense of connection and meaning. The ability to adjust to various literacy levels, cultural backgrounds, and individual preferences renders it an effective community-based intervention. The findings emphasize the capacity of bibliotherapy to meet mental health requirements in urban Pakistan and advocate for its incorporation into library services, educational settings, and wellness programs led by NGOs.